Receptor binding mode and pharmacological characterization of a potent and selective dual CXCR1/CXCR2 non-competitive allosteric inhibitor - Bertini, R. (2012)
Background and Purpose: DF 2156A is a new dual inhibitor of IL-8 receptors CXCR1 and CXCR2 with an optimal pharmacokinetic profile. We characterized its binding mode, molecular mechanism of action and selectivity, and evaluated its therapeutic potential. Experimental Approach: The binding mode, molecular mechanism of action and selectivity were investigated using chemotaxis of L1.2 transfectants and human leucocytes, in addition to radioligand and [ 35S]-GTPγS binding approaches. The therapeutic potential of DF 2156A was evaluated in acute (liver ischaemia and reperfusion) and chronic (sponge-induced angiogenesis) experimental models of inflammation. Key Results: A network of polar interactions stabilized by a direct ionic bond between DF 2156A and Lys99 on CXCR1 and the non-conserved residue Asp 293 on CXCR2 are the key determinants of DF 2156A binding. DF 2156A acted as a non-competitive allosteric inhibitor blocking the signal transduction leading to chemotaxis without altering the binding affinity of natural ligands. DF 2156A effectively and selectively inhibited CXCR1/CXCR2-mediated chemotaxis of L1.2 transfectants and leucocytes. In a murine model of sponge-induced angiogenesis, DF 2156A reduced leucocyte influx, TNF-α production and neovessel formation. In vitro, DF 2156A prevented proliferation, migration and capillary-like organization of HUVECs in response to human IL-8. In a rat model of liver ischaemia and reperfusion (I/R) injury, DF 2156A decreased PMN and monocyte-macrophage infiltration and associated hepatocellular injury. Conclusion and Implications: DF 2156A is a non-competitive allosteric inhibitor of both IL-8 receptors CXCR1 and CXCR2. It prevented experimental angiogenesis and hepatic I/R injury in vivo and, therefore, has therapeutic potential for acute and chronic inflammatory diseases.